ANALISA SITASI ARTIKEL ILMIAH DOSEN UNIVERSITAS LANCANG KUNING PADA GOOGLE SCHOLAR - Izza, Nurul; Sudiar, Nining; Latiar, Hadira (Jurnal Al- Ma'arif : Ilmu Perpustakaan dan Informasi Islam, 2024)
This research aims to find out how to cite scientific articles by Lancang Kuning University lecturers in online journals published in 2019-2021. The research method used is descriptive quantitative research. The data collection techniques using observation, documentation and literature study. The results of the study show that the total number of articles opened was 2,340 articles, the number of articles in 2019 opened with 611 articles, the number of articles in 2020 opened with 811 articles, and the number of articles in 2021 which opened 918 articles. The highest number of articles per faculty is from the Faculty of Engineering with a total of 440 articles, while the lowest number of articles is from Postgraduate with a total of 82 articles. The number of articles cited was 761 articles and the number of articles that were not cited was 1,579 articles, while the number of articles cited was opened 2,479 citations. The highest number of articles cited was in 2019 with a total of 311 articles and the lowest number of articles in 2021 was 152 articles. and 5 subject articles that are frequently cited, namely the first with the subject of Sales Information Systems 101 citations. The second with the subject Indonesian Throughflow obtained 45 citations. Third, with the subject of Training which was opened in 2020, four with the subject of K-Means Alghoritm recording 31 citations, and the fifth with the subject of Corporate Social Responsibility (CSR) with a total of 27 citations.